Alignment between informal educator perceptions and audience expectations of climate change education. Issue 4 (2nd October 2017) - Stylinski, Cathlyn; Heimlich, Joe; Palmquist, Sasha; Wasserman, Deborah; Youngs, Renae
ABSTRACT: To understand the complexities of climate change on educator-visitor relationships, we compared educators' perceptions with audiences' expectations for informal science education institutions. Our findings suggest two disconnects: (a) a professional recognition that climate change education is related to institutional mission but a lack of intentional integration of this issue into programming and (b) a misalignment between what educators believe visitors "need to know" and what visitors say they "need to know." These findings indicate institutions' need to discuss how climate change topics integrate with ongoing education efforts and how to best approach messaging and support staff to meet audience expectations.